Pemanfaatan Energi Geothermal dalam Perspektif Etika Linkungan Meng Zi: Menuju Keharmonisan Manusia dan Alam - Selestianus Bhago Raso; Pasi, Yohanes Eufo Jawa; Mbake, Yohanes Nelson (Pusat Riset dan Inovasi Nasional, 2025)
The utilization of geothermal energy as a renewable energy source is growing in an effort to reduce dependence on fossil energy and its negative impact on the environment. However, the exploitation of this natural resource still contains potential ecological risks if not managed wisely. This article examines the use of geothermal energy through the perspective of the environmental ethics of Meng Zi (Mencius), a classical Confucian philosopher, who emphasized harmony between humans and nature. Meng Zi's ethical approach highlights the importance of virtue, moderation and respect for the natural order in every human activity, including energy management. Through a philosophical-critical study, this article shows that the application of Meng Zi's environmental ethics can provide a moral foundation for sustainable and equitable geothermal exploration policies and practices. Thus, the synergy between modern technology and classical ethical wisdom is key to realizing ecological sustainability and harmony.